Функціонування армії в Стародавньому Римі як елемент правопорядку (на прикладі Преторіанської гвардії – Політичної поліції) - Поліщук, Марина Геннадіївна; Поліщук, М. Г.; Polishchuk, Maryna H. (Одеса, 2018)
У статті досліджене становлення римської армії, рівень мілітаризації суспільства, місце армії в повсякденному житті громадян на прикладі історії створення та функціонування преторіанської гвардії. Велика частина успіху припадає на могутність римської армії, яка неодноразово демонструвала майстерно відточені навички як ворожим країнам, так і власному народу. Захист держави був фундаментальною частиною питання функціонування й розквіту Римської імперії.

The study is that the introduction and study of historical sources that indicate the formation and maintenance of the army in ancient Rome, as an important element in the study of the development of the state. Illumination of objective historical facts, reforms and legal aspects of the Roman army, as well as analysis of the functions of the Praetorian Guard. The article consists in a comprehensive coverage of the policies of the Roman Empire and clarification of the integral role of the reform system of the Roman Army. The achievement of this goal involves examining the following tasks: – the nature and content of the policy of Rome; – the process of policy evolution, which was held in the Praetorian Army, – the role of military alliances in this region; – the influence of various factors that contributed to the development of the Praetorian Guard; Ancient Rome is known to us as one of the most powerful civilizations in the world. Much of the success falls on the pow- er of the Roman army, which has repeatedly demonstrated mastery honed skills as hostile countries and their own people. The article examines the formation of the Roman army, the level of militarization of society, the place of the army in everyday life of citizens on the example of the history of the creation and functioning of the Praetorian Guard. Much of the success falls on the power of the Roman army, which has repeatedly demonstrated mastery honed skills as hostile countries and their own people. Protection of the state was a fundamental part of the question of the functioning and prosperity of the Roman Empire. Considering the extraordinary amount of events in the history of ancient Rome, contemporaries can argue that the army played one of the most important roles in everyday life and in armed conflicts or wars. It is impossible not to mention the impressive level of militarization of society at all stages of the formation of Ancient Rome. The level of training of warriors, the elegance of assembly, discipline and loyalty to the ideology of the Roman army serves as an immortal example for modern military organizations.
Поліщук М. Г. Функціонування армії в Стародавньому Римі як елемент правопорядку (на прикладі Преторіанської гвардії – Політичної поліції) / М. Г. Поліщук // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Одеса, 2018. – Вип. 31. – С. 45-48.
Keywords: військовий; призов; зброя; армія; реформи; присяга; преторіанська гвардія; страта; загони; пацифікація; military; prizes; armed; army; reform; oath; praetorian guard; execution; detachments; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects